Part 5b: Solvent chemistry: reaction kinetics of CO2 absorption into reactive amine solutions. Issue 2 (April 2012) - Sema, Teerawat; Naami, Abdulaziz; Liang, Zhiwu; Shi, Huancong; Rayer, Aravind V; Sumon, Kazi Z; Wattanaphan, Pathamaporn; Henni, Amr; Idem, Raphael; Saiwan, Chintana; Tontiwachwuthikul, Paitoon
Reaction kinetics is one of the most important parameters for the amine-based CO2 capture process because it indicates how fast CO2 reacts with amine, and it is one of the key parameters required for simulating and designing the absorption column. Reaction kinetics has been studied for several decades to aid the understanding of the reaction mechanism, obtaining the kinetics data and understanding the kinetics behavior. This article will comprehensively review these research activities from past to present and look at the future perspective of the study of CO2 absorption kinetics.